Anatomical root adaptations to humidity regimes in the high Colombian Andes (2017)
Páramos rise over 3000 meters high in the Andes as the fastest evolving biodiversity hotspot. It is surprising that only few plant anatomy studies have been made in these areas. Considering that, this research consisted of exploring possible adaptations in root anatomy to differences in soil moisture. In order to investigate these adaptations, soil volumetric moisture was measured in different páramo zones. After these procedures, two humidity zones: "wet" and "dry" were distinguished by looking at soil moisture. Twelve congeneric species in six genera (Arcytophyllum, Eryngium, Espeletia, Hypericum, Lachemilla, Paepalanthus) inhabiting wet and dry zones were selected. To visualize and analyze possible anatomical adaptations to changes in soil humidity, we made hand cross-sections of equal-order rootlets. Root anatomical characters associated with water impermeability, storage, and transport were measured as well. We conducted a MANOVA test to find which characters were significatively associated to changes in soil humidity. Root anatomy was characterized for each species...